The role of pharmacogenetics in keloid scar treatment: A literature review - Tamara Searle; Faisal R Ali; Firas Al-Niaimi (SAGE Publishing, 2020)
Background: The pathophysiology of keloid scars is still not fully understood and a universally reliable effective treatment has not been identified. Pharmacogenetics explores how drug response to a particular therapy can relate to genetic variations. Purpose: To investigate how pharmacogenetics could be applied to keloid scars and the relevance of this to clinical practice. Methods: We reviewed the literature and discuss our current knowledge of pharmacogenomics in the treatment of keloid scars. A literature search was performed using the terms 'Pharmacogenetics', 'Pharmacogenomics', 'Keloid' and 'Scar'. We searched the PubMed, MEDLINE and EMBASE databases to find the relevant articles. Only articles in English were chosen. The level of evidence was evaluated and selected accordingly listing the studies with the highest level of evidence first. Results: Treatments including corticosteroid injections and 5-fluorouracil can be effective in some patients, but less so in others. Polymorphisms of the glucocorticoid receptor and variants of CCL2, YAP1 , miR-21-5p and NF-κβ might be responsible for different responses to treatments used in keloid scars such as 5-fluorouracil. Small molecule inhibitors might be utilised to target other implicated genes. Conclusion: Pharmacogenetics aims to produce the most efficacious patient outcomes while reducing adverse effects. Understanding the pharmacogenetics of keloid scars could lead to a new era of personalised medicine in the treatment of keloid scars. At present, there is some evidence (level 3b/4) to suggest genetic variations that are responsible to drug response in keloids, but further research in this field is required. Lay summary The varied response to similar therapeutic treatments in keloids has prompted the consideration of the role of genetic variants on response in the form of pharmacogenetics. Pharmacogenetics refers to drugs and their metabolism and action based on genetic influences. The ideal scenario would involve the selection of treatment based on the individual's specific genetic variants to ensure maximum efficacy with minimal toxicity. Some evidence currently points to genetic variations in some keloid patients that might be of relevance to the treating clinician.